Formulations of Glyphosate Using Oil Based Adjuvants and their Weed Control Efficacy - Al-Eryani, Abdul-Raqeeb Ali Ahmed (2004)
The oillwater isotropic formulations of methyl oleate/water/nonionic surfactants system were obtained through phase diagram study. The results showed that surfactants Agrimul 2067, Agrimul 2069, Speedex, Pulse, Triton X-100, Tween 20, Trycol 5956 and Trycol 5944A lead the solubilization of methyl oleate in water to the formation of isotropic solutions. All surfactants except Pulse exhibited a good tolerance to waterbased isotropic solutions. The organosilicone surfactants (Pulse and Speedex) exhibited intolerant characteristic to the glyphosate isopropylamine salts. In mixed surfactant systems, Triton X- 100 extended greater isotropic regions of methyl oleate/water/Agrimul 2069 and methyl oleate/water/Agrimul 2067 systems compared to Tween 20. Six oil in water isotropic (microemulsion) formulations were selected from the phase diagram study and evaluate for their effectiveness against eight selected weeds. The efficacy of commercial glyphosate ( ~ o u n d u ~w@a)s first established against eight selected species of weeds in the glasshouse. The percentage of mortality and spray deposition significantly linearly increased with increasing rates of glyphosate. The EDso of glyphosate on the weed species indicated variable tolerance and ranked as follows: Diodia ocimifolia (0.95 kg a.e ha-') z Cyperus rotundus (0.78 kg a.e ha-') 2 Eleusine indica (0.77 kg a.e ha-') > Imperata cylindrica (0.71 kg a.e ha-') > Paspalum conjugatum (0.60 kg a.e ha-') > Asystasia gangetica (0.56 kg a.e ha-') > Mikania micrantha (0.53 kg a.e ha-') > Borreria latifolia (0.34 kg a.e ha-'). These dosages were used to compare with the performance of methyl oleate-water-nonionic surfactant glyphosate formulations. Nine glyphosate formulations, including adjuvant methyl oleate, alkyl polyglycoside, tallow amine (standard), ammonium sulfate, and Triton were prepared and used in the spread area and effectiveness study. In the study of spreading properties of spray droplet on leaf surface, the wax of the weed leaf was determined by two methods of extraction. The extraction of wax using warm chloroform at 40°C and chloroform at room temperature did not show any significant difference among weed species. However, there was a significant different of wax weight between weed species used in this experiment. The amount of wax of the weeds could be ranked as high, medium and low with I. cylindrica (49.46 pg ~ m - ~M)., m icrantha (48.14 pg ~ m - ~E). ,in dica (45.63 pg ~ m -a~nd) C . rotundus (38.69 pg ~ m -b~ein)g in the high category, A. gangetica (23.16 pg ~ m -a~nd) P . conjugatum (22.37 pg ~ m -in~ t)he medium category and D. ocimifolia (14.21 pg ~ m - a~nd) B . latifolia (15.21 pg ~ m -in~ t)he low category. In the spread area and coefficient study, E. indica, A. gangetica and D. ocimifolia were selected to represent the high, medium and low wax respectively. The presence of methyl oleate, Agrimul 2067, Agrimul 2069 and mixed with Triton X-100 in glyphosate formulations significantly increased the spread area and spread coefficient on leaf surfaces of E. indica, A. gangetica and D. ocimifolia compared to water and Roundup@. In the efficacy study, adding methyl oleate, Agrimul 2067 and Agrimul 2069 in the glyphosate formulation gave equal performance as ~ o u n d u ~fo@r th e control of C. rotsrudais, I. cyliudrica, P. conjugaturn, M. micrantha and B. latifolia. All microemulsion formulations showed significantly greater control of D. ocimifolia. In addition, the glyphosate formulation of ME4, ME5 and ME6 performed better than standard Roundupm in controlling A. gangetica and ME6 increased the efficacy of glyphosate for the control of E. indica.